Hematological Performances of Catfish ‘SANGKURIANG’ (Clarias gariepinus, Burch.) Fed on Deits Containing Organic Chromium - Hastuti, Sri; Subandiyono, Subandiyono (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
A research on hematological performances and body immunity of catfish ‘sangkuriang’ (Clarias gariepinus, Burch.) fed on diets containing different levels of organic chromium was conducted.  Three thousands of experimental fishes with their body weight varied from 6 to 7 grams were reared for 40 days in (2x1x1)-m3 of plastic-lining wooden tanks.  The stocking density used was 200 fishes per tank.  The tanks, with a total number of 15 tanks, were connected to each others and to a filtration concrete pond of (5x1x1) m3 to become a semi-closed water system.  The filtered water was pumped up to an every single tank through 1”-PVC pipe as an inlet.  The pipe of each tank was facilitated by a tap to enable controlling its water flow.  During the fish rearing period, a daily siphon was done to clean the fish fesses out from the system.  Diets containing 5 different levels of organic chromium, i.e. 0, 1.5, 3.0, 4.5, and 6.0 ppm of Cr+3, were fed to the experimental fish  thirth a day at satiation.  Each unit of treatment was replicated 3 times.  At the end of rearing period, variables i.e. leucocytes, erythrocytes, hemoglobin, and blood  glucose levels at fasting state were measured for the each treatment.  Results showed that the fish fed on dietary organic chromium tended to improve its body immunity and decrease its total account of leucocytes and its blood glucose level.  Bloods of the fish with dietary organic chromium also tended to contain lower erythrocytes, hemoglobin, hematocryte, and thrombocytes levels than those of the control (i.e. the fish fed on a diet without organic chromium).  The fish which consumed a diet containing 1.5 ppm of Cr+3 showed better hematological performances. Keywords: Hematology, Immunity, Blood glucose, Chromium, Catfish, Sangkuriang, Clarias